2019
DOI: 10.3390/geosciences10010018
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Peak Impact Force for Buildings Exposed to Structural Pounding during Earthquakes

Abstract: Structural pounding between adjacent, insufficiently separated buildings, or bridge segments, has been repeatedly observed during seismic excitations. Such earthquake-induced collisions may cause severe structural damage or even lead to the collapse of colliding structures. The aim of the present paper was to show the results of the study focused on determination of peak impact forces during collisions between buildings exposed to different seismic excitations. A set of different ground motion records, with va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 41 publications
0
14
0
Order By: Relevance
“…Therefore, considering the design earthquake, it is advisable to individually determine the peak impact force of the building exposed to the impact of the structure during the ground movement for a particular con guration of structures. (Khatami et al, 2020). So far, in order to calculate the necessary seismic separation distance between neighboring buildings, much research has been conducted, each of which has presented a new formula, and in some of them, the effect of the period of colliding structures has been considered (Naderpour et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, considering the design earthquake, it is advisable to individually determine the peak impact force of the building exposed to the impact of the structure during the ground movement for a particular con guration of structures. (Khatami et al, 2020). So far, in order to calculate the necessary seismic separation distance between neighboring buildings, much research has been conducted, each of which has presented a new formula, and in some of them, the effect of the period of colliding structures has been considered (Naderpour et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, considering the design earthquake, it is advisable to individually determine the peak impact force of the building exposed to the impact of the structure during the ground movement for a particular configuration of structures. (Khatami et al 2020). So far, in order to calculate the necessary seismic separation distance between neighboring buildings, much research has been conducted, each of which has presented a new formula, and in some of them, the effect of the period of colliding structures has been considered (Naderpour et al 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Earthquakes, however, keep deepening the knowledge of the scientific community and keep raising the awareness of the scientific, technical and political community to the need of identifying assets at risk (i.e., such adjacent buildings) and developing more effective risk mitigation strategies. Based on the provided lessons from major earthquakes, a vast body of literature addressing the pounding effects on the structural response of adjacent structures during earthquakes have been found over the past five decades (e.g., see [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19] among others). The research on earthquake-induced pounding was found in different scales; from studying the impact phenomena to the global performance of the adjacent structures.…”
Section: Introductionmentioning
confidence: 99%